Perancangan dan Pengembangan E-Financial Transaksi Sewa Gedung Menggunakan Framework Laravel - Teguh Kurniawan; Ahmad Syarif; Rahmad Aulia; Bagus Aji Pratama (Jurnal Informatika Universitas Pamulang, 2019)
The building is a place that is much needed in our daily lives, people choose the building as a place to conduct an event such as a wedding reception, seminar or other event activities. In the process of renting buildings many building providers still use conventional methods in building rental booking transactions, namely by keeping a bookkeeping process of existing rental transactions, this has an impact on recording financial income (financial recapitulation) of building transactions that occur frequently calculation error occurred. This study aims to facilitate the people in the process of leasing building transactions online and build information systems that are able to automatically recapitulate finances based on existing transactions so as to minimize human errors made using the laravel framework. The system was built using the SDLC (System Development Life Cycle) method as well as data collection which was carried out in a study of literature, observation and interviews, with this system making the process of building lease transactions even better than the previous system.